Duality of interaction outcomes in a plant–frugivore multilayer network - Genrich, Christiane M.; Mello, Marco A. R.; Silveira, Fernando A. O.; Bronstein, Judith L.; Paglia, Adriano P. (Oikos, 2017)
In plant–animal interactions, species are commonly labeled as either mutualists or antagonists, based on the most common, most studied, or most easily observed outcome. Nevertheless, evidence from simple systems comprising 2–4 species suggests that those labels are an oversimplification: individual species often function in both roles, either simultaneously or at different places or times. We include both mutualistic and antagonistic interactions between mammals and seeds in a multilayer network, to explore for the first time the community-level consequences of the dual roles played by some species. We tested whether negative and positive interactions within a plant–frugivore network are separated into different modules, or whether they overlap due to the presence of frugivores that both kill and disperse seeds. The frugivorous diets of nonvolant small mammals were studied at one dry tropical forest site in southeastern Brazil by analyzing fecal samples from individuals captured in live traps. Seed viability was assessed with a tetrazolium test to determine the outcome of those interactions, as estimated by whether or not seeds survived gut passage. Interactions were analyzed as a weighted multilayer network, subdivided into one potentially mutualistic (live seeds deposited) and one antagonistic (dead seeds deposited) layer. The two layers had similar structure with high overlap between them. Some mammal species exhibited highly central, dual roles, acting both as antagonists and mutualists, in many cases of the same plant species. Dispersal service by most of these small mammals is accompanied by seed destruction, suggesting that the selective pressures exerted by those animals on the plants is much more complex than often assumed. Our results demonstrate that the complexity of plant–frugivore networks can not be fully understood without proper incorporating measures of seed fate following gut passage.